2019
DOI: 10.1536/ihj.18-337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicorandil on All-Cause Mortality and Cardiac Events in CAD Patients Receiving PCI

Abstract: Current studies demonstrating the effects of nicorandil in the prognosis of coronary artery disease (CAD) patients who received percutaneous coronary intervention (PCI) are inconclusive due to the small sample size and small events rate. PubMed, OVID, CBM and CNKI databases were searched using a pre-specified search string to collect randomized controlled trials (RCTs) studying the effects of nicorandil on CAD patients receiving PCI. Data on all-cause mortality and cardiovascular events were collected. RevMan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Studies have suggested that reperfusion arrhythmias are non-invasive indicators of myocardial cell damage. 24 In the current study, no patient died and no significant changes were seen in Echo 48 hours post-PCI, but nicorandil showed overall better outcomes compared to the control group, which was in line with Zhang et al 25 The current results agreed with the findings of a randomised trial that had a 5-year follow-up in which nicorandil was given 20-30 minutes before PCI as an IV infusion of 12mg in 100ml of saline. The study found that a single dose of nicorandil improved not only early but also late clinical events, including cardiovascular death or hospital admission due to worsening congestive heart failure (CHF).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have suggested that reperfusion arrhythmias are non-invasive indicators of myocardial cell damage. 24 In the current study, no patient died and no significant changes were seen in Echo 48 hours post-PCI, but nicorandil showed overall better outcomes compared to the control group, which was in line with Zhang et al 25 The current results agreed with the findings of a randomised trial that had a 5-year follow-up in which nicorandil was given 20-30 minutes before PCI as an IV infusion of 12mg in 100ml of saline. The study found that a single dose of nicorandil improved not only early but also late clinical events, including cardiovascular death or hospital admission due to worsening congestive heart failure (CHF).…”
Section: Discussionsupporting
confidence: 91%
“…Almost 90% of patients developing doxorubicinmediated LVEF deterioration never fully recover complete cardiac function even with these therapies. Nicorandil, the first nitrate compound and ATP-dependent potassium (K + ATP) channel opener applied clinically as a new vasodilator treatment [32,33], has multiple cardiovascular benefits for multiple heart diseases and improved cardiac function [34][35][36]. Nicorandil suppresses the inflammatory cytokines IL-1β, IL-1, IL-6, IL-10, IL-18, IL-19 and TNF-α in acute coronary syndrome patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…RIPC means that non-lethal and reversible ischemia and reperfusion affecting one organ or tissue alone provide a "preconditioning" effect against a following severe ischemia-reperfusion applied to another organ or tissue, causing its hypoxic death (11). ATP-sensitive potassium channels are active in place of mitochondria, doing a job similar to that of the preconditioning of ischemic (12). Therefore, the present study focused on nicorandil efficacy and safety, which were underlined for preventing periprocedural myocardial injury in patients who had undergone PCI.…”
Section: Introductionmentioning
confidence: 99%